PERAN BISNIS DIGITAL DALAM MENINGKATKAN PENJUALAN DAN KEPUASAN PELANGGAN PADA DIMSUM NYAMEE.ID PALU - Dian Safita; Erwinsyah; Phatra Anggana Djuri; Femilia Zahra (Publika Citra Media, 2025)
Digital transformation through social media has become a strategic tool for micro, small, and medium enterprises (MSMEs) to enhance their adaptability in the era of technology. This study examines the implementation of digital business systems by Dimsum Nyamee.id Palu through WhatsApp, Instagram, and TikTok, focusing on increasing sales and customer satisfaction. The research employs a descriptive qualitative approach with data collection methods including in-depth interviews, observations, and documentation. The findings reveal that the daily pre-order system integrated with social media simplifies the ordering process, improves production efficiency, and strengthens communication with customers. Digital marketing strategies that rely on informative and interactive content have proven effective in expanding market reach and enhancing customer loyalty. Customers expressed satisfaction with service quality, ordering convenience, and the responsiveness of the admin. This study demonstrates that simple yet well-directed digitalization can significantly improve the operational performance and services of MSMEs. The findings also hold important implications as evidence that social media can serve as a strategic tool in supporting the development of MSMEs. Moreover, the results can serve as a reference for business practitioners and policymakers in formulating relevant and sustainable digital transformation strategies.